Postmastectomy radiation therapy following pathologic complete nodal response to neoadjuvant chemotherapy: A prelude to NSABP B-51?. (September 2021) - Haque, Waqar; Singh, Anukriti; Verma, Vivek; Schwartz, Mary R.; Chevli, Neil; Hatch, Sandra; Desai, Monica; Butler, E. Brian; Arentz, Candy; Farach, Andrew; Teh, Bin S.
Highlights: PMRT was not associated with an overall survival benefit in all patients. Number of lymph nodes removed was not associated with overall survival. PMRT improved overall survival in patients with cT3-4 and cN3 disease. Abstract: Purpose: The utility of post-mastectomy radiotherapy (PMRT) in women with a nodal complete response (CRn) to neoadjuvant chemotherapy (NAC) is unknown. The NSABP B-51 trial is evaluating this question, but has not reported results thus far. Therefore, we sought to answer this question with the National Cancer Database. Methods: The National Cancer Database was queried for women with cT1–4N1-3M0 breast cancer who had undergone NAC and were ypN0 upon mastectomy. Statistics included multivariable logistic regression, Kaplan-Meier overall survival (OS) analysis, Cox proportional hazards modeling, and construction of forest plots. Results: Of 14, 690 women, 10, 092 (69%) underwent adjuvant PMRT and 4598 (31%) did not. The median follow-up was 55.6 months. In all patients, the 10-year OS was 76.3% for PMRT and 78.6% without ( p = 0.412). There were no notable effects of PMRT on OS based on age or the axillary management (number of nodes removed). Specifically, in the NSABP B-51 population of cT1–3 cN1 patients, the 10-year OS was 82.6% for PMRT and 80.0% without ( p = 0.250). PMRT benefitted women with increasing cT stage (i.e. cT3–4), increasing ypT stages (with the exception of ypT4 potentially owing to small sample sizes), and cN3 cases ( p < 0.05 for all). Conclusions: In the absence of published results from NSABP B-51, this assessment of over 14, 000 women from a contemporary US database revealed that PMRT may be most useful for a "moderately-high" risk group – women with more advanced primary and/or nodal disease at diagnosis, yet with tumor biology favorable enough that the disease does not progress or remain stable after NAC. The OS findings notwithstanding, this study cannot exclude potential differences between groups in recurrence-free survival, which is the primary endpoint of NSABP B-51, While the results of the NSABP B-51 will confirm optimal management for patients with limited nodal disease having a CRn following NAC, the present results suggest PMRT should remain the standard of care for more advanced disease than NSABP B-51 eligibility criteria.